Antibiograms, toxin profiling and molecular typing of Staphylococcus aureus isolates from two tertiary hospitals in Jordan - Jaradat, Ziad W; Hamdan, Thamer A; Hayajneh, Wail; Al Mousa, Waseem; Al Shehabi, Asem (Journal of infection in developing countries, 2017)
Introduction: Methicillin-resistant Staphylococcus aureus (MRSA) is a major cause of hospital-associated infections. This study was undertaken to investigate toxin profiles as well as antibiotic resistance patterns of S. aureus isolates form two tertiary hospitals in Jordan. Methodology: A total of 250 S. aureus isolates from clinical samples of two tertiary hospitals were analyzed for the presence of the mecA, vanA, vanB, and 16 Staphylococcus toxin encoding genes using PCR. The isolates were further tested for antimicrobial sensitivities using the disc diffusion method. DNA from all the isolates were fingerprinted by coa gene Restriction Fragment Length Polymorphism (RFLP) to study relationships between isolates from the two hospitals. Results: 73.2% of the isolates contained the mecA gene and thus were designated MRSA. All MRSA isolates showed high levels of resistance to many of the antibiotics compared to those of MSSA. All MRSA isolates were susceptible to vancomycin and teicoplanin while all MSSA isolates were susceptible to nitrofurantoin, teicoplanin, vancomycin, cefoxitin, clindamycin, erythromycin and gentamycin. The isolates exhibited high prevalence of the toxin genes and none of the isolates contained less than 4 genes with one isolate contained 14 genes with no apparent differences in gene profiles among MRSA and MSSA. About 60% of the isolates contained 12 to 13 toxin genes and were isolated either from pus or blood. Conclusion: Antibiograms of the MRSA isolates were significantly different from MSSA antibiograms while there were no apparent differences in the toxin genes profiles. Further, coagulase gene RFLP of the isolates showed that the isolates are very heterogenic.